The judicial politics of Burqa Bans in Belgium and Spain: socio-legal field dynamics and the standardization of justificatory repertoires - Burchardt, Marian; Yanaşmayan, Zeynep; Koenig, Matthias (Law & social inquiry, 2019)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0897654618000096/resource/name/firstPage-S0897654618000096a.jpg